THE INTERVENSI MICRO WAVE DIATHERMY DAN SLOW STROKE BACK MASSAGE LEBIH EFEKTIF DIBANDINGKAN DENGAN MICRO WAVE DIATHERMY DAN WILLIAM FLEXION EXERCISE DALAM MENINGKATKAN KEMAMPUAN FUNGSIONAL PADA KASUS MYOGENIC LOW BACK PAIN - Juniantari, Ni Komang Ayu; Kinandana, Gede Parta; Saraswati, Putu Ayu Sita; Winaya, I Made Niko (Majalah Ilmiah Fisioterapi Indonesia; Vol 6 No 2 (2018): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2018.v06.i02.p11, 2018)
ABSTRACT Myogenic low back pain is a syndrome of lower back pain caused by tension of the muscles around the lower back and is a work related musculoskeletal disorder. The purpose of this study was to identify the difference in effectiveness between slow stroke back massage and William flexion exercise on the improvement of functional ability in individual with myogenic low back pain. This research is an experimental study with pre and post test control group design. The sample size is 36 people divided into two groups. Group 1 was given slow stroke back massage intervention and Group 2 was given intervention of William flexion exercise. Both groups received microwave diathermy intervention as initial therapy. Measurement of lower back functional ability using MOLDBQ. The hypothesis was tested using paired sample t-test obtained p = 0,000 with pre and post difference is 20,12 ± 1,445 in Group 1, whereas in Group 2 the result p = 0.000 with pre and post difference is 9.94 ± 0.854. Comparison was tested using independent sample t-test with the difference obtained was p = 0,000 (p <0,05). Based on statistical test results, it can be concluded that slow stroke back massage intervention is more effective in improving functional ability compared to William flexion exercise in individual with myogenic low back pain. Keywords: myogenic low back pain, slow stroke back massage, William flexion exercise, microwave diathermy, MOLDBQ